The Differences between Key Words-Pictorial and After Reading Card Methods in English Vocabulary Mastery - Devi Kurnia Lianto; Dayu Retno Puspita (Universitas Ahmad Dahlan, 2019)
This study aims to determine the differences in English vocabulary skills of students using the Keywords-Pictorial learning method with students who use the After Reading Card Game learning method. This study used a quasi-experimental research method with the study of Nonequivalent Control Group Design. The population subjects in this study were all of the fifth grade students of MI Al-Istiqomah, Tangerang City, which numbered 50 students, taking a sample of 25 students in the first experimental class and 25 students in the second experimental class. The technique of collecting data using test questions instruments describing vocabulary skills consists of 20 valid and realistic questions. Based on the results of the study, testing the posttest hypothesis from the results of the t-test obtained tcount = 29.05 and table = 2.02, it can be concluded that there are significant differences between the posttest grade values of the first experimental class and the second experimental class. This can be interpreted that the English vocabulary abilities of students using the After Reading Card Game learning method are higher with students who use the Keywords-Pictorial learning method.Â Keywords: Keywords-Pictorial method; After Reading Card Game, mastery of vocabulary